2017
DOI: 10.1080/00268976.2017.1384579
|View full text |Cite
|
Sign up to set email alerts
|

A DFT approach to discriminate the antagonist and partial agonist activity of ligands binding to the NMDA receptor

Abstract: Index S2 2D molecular structures S3 Global descriptors S7 Local descriptors S11 Comparison of global molecular descriptors S17 Correlation plot for chemical hardness S18 Comparison of local molecular descriptors S19 Efficacy of partial agonists S22 Cartesian coordinates of partial agonists (zwitterion)-B3LYP S23 Cartesian coordinates of partial agonists (zwitterion)-M06-2X S42 Cartesian coordinates of partial agonists (neutral)-B3LYP S48 Cartesian coordinates of antagonists-B3LYP S67 Cartesian coordinates of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Many scholars proposed that the activity of agonists for the GABA A receptor at BZD sites was closely related to the electron transfer in the frontier molecular orbital, and the electron transfer participated in BZD activity by the mode of action in cell signaling. , To further explain the different activities of YPVEPF and its metabolites, the electronic characteristics were calculated by a quantum mechanical (QM) assay. QM property fields were commonly used to understand novel structure–activity relationship features in many studies. As shown in Figure , the Mulliken electronegativity χ values of YPVEPF and YPVEP (80.22 and 78.45 kcal/mol, respectively) were lower than those of PVEPF and PVEP (85.51 and 84.29 kcal/mol, respectively), indicating that the peptides YPVEP and YPVEPF had relatively higher electron-donating ability compared with PVEPF and PVEP. In addition, the results showed that the HOMO and LUMO states for the four peptides were all considerably set apart and localized on the right and left half of the peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Many scholars proposed that the activity of agonists for the GABA A receptor at BZD sites was closely related to the electron transfer in the frontier molecular orbital, and the electron transfer participated in BZD activity by the mode of action in cell signaling. , To further explain the different activities of YPVEPF and its metabolites, the electronic characteristics were calculated by a quantum mechanical (QM) assay. QM property fields were commonly used to understand novel structure–activity relationship features in many studies. As shown in Figure , the Mulliken electronegativity χ values of YPVEPF and YPVEP (80.22 and 78.45 kcal/mol, respectively) were lower than those of PVEPF and PVEP (85.51 and 84.29 kcal/mol, respectively), indicating that the peptides YPVEP and YPVEPF had relatively higher electron-donating ability compared with PVEPF and PVEP. In addition, the results showed that the HOMO and LUMO states for the four peptides were all considerably set apart and localized on the right and left half of the peptides.…”
Section: Resultsmentioning
confidence: 99%